The Influence of Financial Attitude, Financial Knowledge, and Personal Income on Personal Financial Management Behavior - SYARIF, AZMI; Putri, Anne (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This research aims to analyze the effect of financial attitude, financial knowledge, and personal income on personal financial management behaviorMethodology/approach – This research uses quantitative methods. Data processing and hypothesis testing using SmartPLS Version 3.2.9. This research was conducted at PT. Bank Tabungan Negara (Persero) Tbk Padang Branch, West Sumatra Province, Indonesia. The sampling technique used is the saturated sampling technique. The sample used is 92 respondents.Findings – It was found that. financial attitude and financial knowledge have a positive and significant effect on personal financial management behavior. Personal income has a positive and insignificant effect on personal financial management behavior.Novelty/value – financial attitude, financial knowledge are important factors that influence personal financial management behavior. While personal income does not affect personal financial management behavior. However, these indicators remain important in improving personal financial management behavior, especially by paying attention to indicators of financial attitude, financial knowledge and personal income.